TEACHING ENGLISH FOR TOURISM TO MEET LEARNERS’ NEEDS - Nha, Vu Thi Thanh (VNU Journal of Foreign Studies, 2018)
This paper analyses students’ needs for English for Tourism courses at three universities in Vietnam. It reveals that need assessments can be conducted in three different approaches: Target needs analysis, present needs analysis and holistic needs analysis. In this study, the author conducted an online survey with 158 students to analyse the present needs of the students. The findings show that the students think they need to improve their communicative English and content knowledge in Tourism. They expect to involve more project work to increase practical language use opportunities. These findings can be used to adjust the current courses to better meet the students’ needs.